Feasibility study on use of solar energy in Malaysia's light rail transit - Omar W.A.W.; Hayder G.; Aldrees A.; Taha A.T.B. (IOP Publishing Ltd, 2023)
Climate change; Disasters; Electric power transmission networks; Pollution; Sea level; Solar cell arrays; Solar energy; Solar power generation; Urban transportation; Water supply; Climate change impact; Electric power supply; Environmental pollutions; Feasibility studies; Light rail transit (LRT); Renewable energies; Renewable sources; Urban public transportations; Light rail transit